1962
DOI: 10.1111/j.1365-2621.1962.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Olfactory Threshold Concentration and Pyruvic Acid Content of Onion Juice

Abstract: A highly significant correlation (r = -0.97) exists between the amount of enzymatically developed pyruvie acid present in the juice of comminuted onion and the olfactory threshold concentration of the juice. The eorrelation indicates that determination of pyruvic acid in freshly prepared onion juice constitutes a fairly reliable, simple, and convenient method of estimating at least one aspeet of onion flavor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(39 citation statements)
references
References 9 publications
3
36
0
Order By: Relevance
“…Soluble solids content was strongly correlated with onion dry weight: r = 0.95 (Vågen and Slimestad, 2008) and r = 0.98 (Jaime et al, 2001); while, matching up with our results, the correlation between dry weight content and pyruvate content was found to be quite low (r = 0.38) (Vågen and Slimestad, 2008). Other authors have also found a medium correlation (r from 0.42 to 0.57) (Schwimmer and Guadagni, 1962;Lin et al, 1995;Galmarini et al, 2001). In contrast, Yoo et al (2006) indicated that there was no consistent trend between these traits in four different clones grown at Weslaco.…”
Section: Relation Among the Evaluated Traitssupporting
confidence: 74%
“…Soluble solids content was strongly correlated with onion dry weight: r = 0.95 (Vågen and Slimestad, 2008) and r = 0.98 (Jaime et al, 2001); while, matching up with our results, the correlation between dry weight content and pyruvate content was found to be quite low (r = 0.38) (Vågen and Slimestad, 2008). Other authors have also found a medium correlation (r from 0.42 to 0.57) (Schwimmer and Guadagni, 1962;Lin et al, 1995;Galmarini et al, 2001). In contrast, Yoo et al (2006) indicated that there was no consistent trend between these traits in four different clones grown at Weslaco.…”
Section: Relation Among the Evaluated Traitssupporting
confidence: 74%
“…Pyruvate concentrations from the high S treatment are representative of phenotypic differences previously reported for fieldgrown fresh market onions, although values below 5 .3gmol .g -1 f .w . were rare (Bajaj et al ., 1980 ;Freeman & Whenham, 1975 ;Lancaster et al ., 1988 ;Schwimmer & Guadagni, 1962 ;Schwimmer & Weston, 1961) . Phenotypic variability for enzymatic pyruvate at low S fertility has not been previously described .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one can conclude that the odour strength of onion did increase upon S fertilization. A good correlation was proven to exist between odour strength and the pyruvic acid content of bulbs [16]. This could be attributed to the differential partition of sulfur fertilization into flavour and non-flavour compounds in the onion bulbs [3].…”
Section: Onion Order Strengthmentioning
confidence: 90%